Ulicą Byszewską do Skoszew w gminie Nowosolna w powiecie łódzkim wschodnim - Szymczak, Jan (Zeszyty Wiejskie, 2016)
In Nowosolna commune (Neu-Sulzfeld) near Lodz the greatest importance in the past belonged to Skoszewy, today’s Old Skoszewy that received city rights in 1426 two years after Lodz. In the middle of the road from Nowosolna to Skoszewy there is a village called Byszewy, recorded in 1389. In the sixteenth century it was divided into Byszewy Large with a mill and Byszewy Small. The land was developed to Jaroszki village and currently unknown Drożęcin. Plichtów was developed from Byszewy and Moskwa. Byszewy since the Middle Ages had belonged to the parish in Old Skoszewy. In 1686 Jan Plichta from Kołacin coat Półkozic bought a farm called Byszewy. His descendant was Teodor Plichta (c. 1755–1833), the owner of Byszewy and Moskwa, who at the beginning of the nineteenth century, erected a brick mansion in Byszewy. It appeared in the works of Jaroslaw Iwaszkiewicz, as “manor with four columns”.